Effects of Site Preparation Methods on the Establishment and Natural-Regeneration Traits of Scots Pines (Pinus sylvestris L.) in Northeastern Poland - Marta Aleksandrowicz-Trzcińska (Forests, 2018)
While some tree species can regenerate naturally without mechanical site preparation (MSP), Scots pine has been shown to benefit from this process. We compared three methods: using a double-mouldboard forest plough (FP), an active single-disc plough (AP), and a forest mill (FM), as well as a no-MSP control, in terms of growth, survival and density of occurrence of pines during the first 4 years of natural regeneration. Moisture conditions were expressed via calculated de Martonne aridity indices, while the microhabitats generated via different MSP methods were further characterised by the total contents of N and C, and the C/N ratio, P2O5, and base cations, as well as bulk density and actual moisture. The trials showed inferior regeneration without MSP in terms of the density and cover of young pines. Any of the studied treatments influenced survival, though the best growth was achieved by seedlings using the FP and AP methods, while the best density and evenness results were obtained using AP. The factors most influencing regeneration features were high precipitation during the first growing season after sowing and reduced competition with other vegetation in the cleared area. This impact seems far more important than the capacity of different MSPs to produce differentiation in soil microhabitats in terms of nutrient status or bulk density.